Determination of fungal and parasitic infections caused vaginitis: molecular identification of Candida parapsilosis in Al-Nasiriyah city, Iraq (Baghdad Science Journal, 2023)
The current study aims to determine the prevalence of Trichomonas vaginalis and Candida spp., and also to identify Candida parapsilosis and some virulence genes. It was conducted in Bint Al-Hoda Hospital of Maternity and Children in Thi-Qar province, south of Iraq for the period from the beginning of January to the end of December 2020. Two hundred and fifty samples were collected from the female genital tract for women whose age ranged between 17-50 years. Microscopic, traditional and molecular tests were used in the sample examination. The results recorded 12 (4.8%) samples infected with T. vaginalis parasite, whereas 130 (52%) samples showed Candida yeast distributed as follows: 75 (30 %) C. albicans, 20 (8%) C. krusei, 14 (5.6%) C. parapsilosisas, 11 (4.4 %) C. glabrata and 10 (4%) C. tropicalis. A 18S rRNA gene of C. parapsilosisas appeared in all samples confirmed with biochemical tests and CHROM agar Candida. The cph1 and hwp1 genes were observed in all of C. parapsilosis isolates (100%), whereas sap1 and plb1 genes showed different proportions (64.3% and 57.1%, respectively). Depending on phylogenetic analysis, there was a slight genetic variation between local isolate sequences compared with global recorded strains.  The current study confirmed that 18S rRNA gene is highly precise to identify C. parapsilosis. The appearance or absence of the genetic variation of some virulence genes may cause different clinical manifestations.